Removal of Hexavalent Chromium Ions from Aqueous Solutions by an Anion-Exchange Resin - P. Senthil Kumar; K. Kirthika; K. Sathish Kumar (Adsorption Science & Technology)
The removal of hexavalent chromium, Cr(VI), from aqueous solutions under different conditions using an anion-exchange resin (AXR) as an adsorbent was investigated under batch conditions. Such studies indicated that the percentage adsorption decreased with increasing initial Cr(VI) concentration, with the maximum removal of such ions occurred at a pH value of ca. 2.0. Both the Langmuir and Freundlich isotherm models were capable of reproducing the isotherms obtained experimentally. The sorption process was rapid during the first 20 min with equilibrium being attained within 30 min. The process followed first-order kinetics. The results demonstrate that such anion-exchange resins can be used for the efficient removal of Cr(VI) ions from water and wastewater.